The Vazante and Canastra groups revisited: Sm-Nd and Sr isotopes - evidence for contribution from Tonian intraplate magmatism during passive margin development along the SW São Francisco margin, Brazil - Carvalho,Manuela de Oliveira (2019)
Abstract Combined Sm-Nd isotope studies and U-Pb ages of detrital zircons have shown significant differences between the provenance patterns of Neoproterozoic metasedimentary successions in the Southern Brasília belt. The Vazante and Canastra groups are passive margin deposits with source areas in the Archean/Paleoproterozoic São Francisco Craton basement and Mesoproterozoic cover units. In literature, the younging trend of Nd model ages observed in the Vazante Group is interpreted as resulting from the contribution of the Neoproterozoic Goiás Magmatic Arc. Also, detrital zircons younger than 0.90 Ga were not recorded in the Vazante or Canastra groups, which zircon populations are older than 0.93 Ga. This work presents new Sm-Nd and Sr isotope data of metasedimentary rocks from the Vazante and Canastra groups, collected in a 400 km2 area in northwest Minas Gerais, Brazil. The improved database of previously published and new data corroborates with the younging pattern of TDM along the Vazante Group. Isochronic diagrams show that samples from Vazante and Canastra groups scatter along mixing lines between the fields defined by the older cratonic rocks and the more juvenile ones. Here we present the Tonian Intraplate Magmatism within the São Francisco Craton as the juvenile source.